2013
DOI: 10.1111/1440-1630.12038
|View full text |Cite
|
Sign up to set email alerts
|

Relocating to retirement living: An occupational perspective on successful transitions

Abstract: This study contributes to literature surrounding how older adults occupy and make meaning of the spaces they call home and also enriches literature regarding environmental transitions. Relocation can be a disruptive process and occupational therapists are uniquely placed to facilitate healthy ageing throughout this transition using preventative and community-based occupational therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 20 publications
(33 reference statements)
4
44
0
Order By: Relevance
“…Searching for familiarity and preference are also seen in studies on social participation (Utz et al, 2002) and leisure participation (Agahi et al, 2006;Hutchinson & Nimrod, 2012). The majority of the literature (Ayalon, 2016;Nuttman-Shwartz, 2008;Pushkar et al, 2010;Utz et al, 2002;Von Bonsdorff et al, 2009;Walker & McNamara, 2013) found positive consequences of MCOA. The third attribute, creating coherence, is essential in maintaining continuity, which is reflective of ego-integrity in internal continuity (Atchley, 1989).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Searching for familiarity and preference are also seen in studies on social participation (Utz et al, 2002) and leisure participation (Agahi et al, 2006;Hutchinson & Nimrod, 2012). The majority of the literature (Ayalon, 2016;Nuttman-Shwartz, 2008;Pushkar et al, 2010;Utz et al, 2002;Von Bonsdorff et al, 2009;Walker & McNamara, 2013) found positive consequences of MCOA. The third attribute, creating coherence, is essential in maintaining continuity, which is reflective of ego-integrity in internal continuity (Atchley, 1989).…”
Section: Discussionmentioning
confidence: 97%
“…A decline in well-being has been observed when people are not able to maintain continuity due to a substantial reduction in income after retirement and the loss of work-related status or respect (Richardson & Kilty, 1991). In another study on the effects of relocation on retirement living, participants' maintenance of routines, relationships, and roles has been found to facilitate optimal person-environment fit throughout the relocation process, although relocation can disrupt security, identity, and social relationships (Walker & McNamara, 2013). Pushkar et al (2010) have tested continuity and activity variables as predictors of positive and negative affect in retirement, and discovered that those who continuously have the same levels of activity can usually maintain positive affect.…”
Section: Uses Of the Concept In The Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…These data show two important trends: the first is related to the strong culture of homeownership that is widespread in the Member States of Southern and Eastern Europe (Lithuania, Hungary, Estonia, Slovenia, Spain, Greece, and Italy) [2]; the second trend clearly evidences the high psychological value that homeownership still has among the older generations in Europe. From this perspective, home is a space threaded with memories and meaning, informing and informed by residents' identity [3][4][5]. It represents a symbol of independence, a place of comfort and security, and a guaranteed asset in case of need.…”
Section: Introductionmentioning
confidence: 99%
“…In moving to a retirement community, the individual breaks from a previous phase of life, and is subject to at least some change in physical and social surroundings and personal and social behaviors (Cutchin, Marshall, & Aldrich, 2010). As a recent review found, “Relocations can be stressful and these environmental transitions can cause significant disruption to the person-environment and occupational fit, thus influencing health, well-being and quality of life” (Walker & McNamara, 2013). Access to healthcare facilities was reported as a main goal by people considering moving into a retirement setting in Australia, and those in poor physical health were more likely to consider moving (Crisp, Windsor, Butterworth, & Anstey, 2013).…”
Section: Introductionmentioning
confidence: 99%